Frequency domain channel estimation and symbol detection for impulse radio ultra-wireband systems with short cyclic prefix - Bahçeci, Salim. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
Frequency Domain (FD) reception techniques provide the telecommunication system designers with low complexity receiver structures. However, when ultra-wideband (UWB) communication is considered with long channel impulse responses adding cyclic prefix (CP) causes decrease in system bandwidth efficiency. Using short cyclic prefix to compensate for bandwidth efficiency lost causes performance lost in terms of bit error rate (BER). In this thesis, we consider iterative cancellation of inter block interference (IBI) caused by short CP usage in impulse radio ultra-wideband (IR-UWB) communication. Pilot blocks aided FD recursive least squares (RLS) channel estimation is considered and an iterative algorithm is proposed for the IBI error cancellation. In addition, for the detection of the transmitted information data blocks a receiver structure is proposed composed of soft input soft output frequency domain minimum mean square error (SISO FD MMSE) equalizer, SISO repetition decoder and IBI estimation block operating in turbo manner.
Keywords: Orthogonal frequency division multiplexing.; Ultra-wideband devices.